Strengthening Religious Moderation Based on Local Wisdom Through Islamic Religious Education in Multicultural Communities in Tanjung Pura District - Hasibuan, Marhan; Hidayat, Muhammad Arif (Maslahah: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to strengthen religious moderation based on local wisdom through Islamic education in the multicultural community of Tanjung Pura District. The region is characterized by high ethnic and cultural diversity; therefore, an inclusive and contextual educational approach is needed. The methods used include socialization, interactive discussions, and training for religious leaders, teachers, and local residents. The results show an increased understanding among participants of the values of religious moderation, such as tolerance, balance, justice, and respect for differences. Furthermore, local wisdom values such as mutual cooperation (gotong royong), deliberation (musyawarah), and mutual respect proved to be effective instruments in strengthening social harmony and cohesion among religious communities. Through cross-community collaboration and Islamic education rooted in local culture, this activity successfully built shared awareness to maintain unity amid diversity. Thus, this program is expected to serve as a model for implementing religious moderation based on local wisdom in other multicultural regions of Indonesia.